Why African Americans say “No”: A Study of Pharmacogenomic Research Participation - Nooruddin, Mohammed (Ethn Dis, 2020)
OBJECTIVE: To identify reasons for nonparticipation by African Americans in cardiovascular pharmacogenomic research. DESIGN: Prospective, open-ended, qualitative survey. SETTING: Research staff approached patients eligible for the Discovery Project of The African American Cardiovascular pharmacogenomics CONsorTium in the inpatient or outpatient setting at four different institutions during September and October 2018. PARTICIPANTS: Potential Discovery Project participants self-identified as African American, aged >18 years, were on one of five cardiovascular drugs of interest, and declined enrollment in the Discovery Project. MAIN OUTCOME MEASURES: Reasons for nonparticipation. METHODS: After declining participation in the Discovery Project, patients were asked, “What are your reasons for not participating?” We analyzed their responses using a directed content analytic approach. Ultimately, responses were coded into one of nine categories and analyzed using descriptive statistics. RESULTS: Of the 194 people approached for the Discovery Project during an eight-week period, 82 declined participation and provided information for this study. The most common reason for refusal was concern about the amount of blood drawn (19.5%). The next most common reasons for refusal to participate included concerns about genetic testing (14.6%) and mistrust of research (12.2%). Across study sites, significantly more patients enrolled in the inpatient than outpatient setting (P<.001). Significantly more women and younger individuals declined participation due to concerns about genetic testing and too little compensation (P<.05). CONCLUSIONS: Collection of blood samples and concerns about genetic testing are obstacles for the recruitment of African Americans to pharmacogenomics studies. Efforts to overcome these barriers to participation are needed to improve representation of minorities in pharmacogenomic research. Enrolling participants from inpatient populations may be a solution to bolster recruitment efforts.